Atlantic Forest Ecosystems: Are There Significant Differences When Compared at the Same Stage of Regeneration? - Bressane, Adriano [UNESP]; Pinto, João Pedro da Cunha [UNESP]; da Silva, Julia Villalta [UNESP]; Silva, Mirela Beatriz [UNESP]; Siminski, Alexandre; Medeiros, Líliam César de Castro [UNESP]; Negri, Rogério Galante [UNESP] (MDPI, 2023)
For the monitoring and assessment of Atlantic Forest ecosystems, key indicators of the regeneration stage are considered. However, the current classification of these stages by experts does not consider the possible differences among such ecosystems. In order to test the hypothesis of significant differences, Atlantic Forest ecosystems in southern Brazil were compared at the same stage (initial, medium, and advanced stages of regeneration). An extensive database of the floristic forest inventory of Santa Catarina state, southern Brazil, with 460 sampling units, was used, addressing the seasonal deciduous forest (SDF), dense ombrophilous forest (DOF), and mixed ombrophilous forest (MOF). The regeneration stage of each sample unit was previously classified by experts using five key indicators (basal area per hectare—BA/ha; number of individuals per hectare—N/ha; number of species—S; Shannon biodiversity index—H’; and diameter at breast height—DBH). The Kruskal–Wallis method and pairwise multiple comparisons based on Dunn’s procedure were applied, considering two-way tests with 5% significance, and 95% power. The statistical tests confirmed the research hypothesis, namely, that the key indicators had significant differences in the later regeneration stages of Atlantic Forest ecosystems. For instance, S in DOF was statistically higher (p < 0.001) than in MOF and SDF (44 ± 9); N in SDF was significantly lower (394 ± 248 at mid-stage) compared to MOF (475 ± 233) and DOF (545 ± 173); and H’ showed increasing differences towards more advanced stages. Considering that the stage of forest regeneration is the main criterion for decision-making between suppression and conservation of forest ecosystems, the results achieved should support the review of current procedures applied to the classification of successional stages. Given the demonstrated differences, in the next steps of research, we will evaluate and propose specific standards for each Atlantic Forest ecosystem, i.e., intervals of discriminating values for the key indicators applicable to this biome.
Keywords: key indicators; monitoring and assessment; regeneration stage